Case Report: Semantic Variant Primary Progressive Aphasia With Impaired Verbal Word Discrimination - Kawakami, Nobuko; Morita, Ayumi; Kanno, Shigenori; Ogawa, Nanayo; Kakinuma, Kazuo; Saito, Yumiko; Kobayashi, Erena; Narita, Wataru; Suzuki, Kyoko (Frontiers in Neurology, 2022)
Primary progressive aphasia (PPA) is associated with various types of hearing impairments. Impaired auditory pattern analysis and word deafness are reported in patients with nonfluent variant PPA (nfvPPA). Conversely, semantic variant PPA (svPPA) does not typically affect auditory pattern perception and does not result in word deafness. Through comprehensive neuropsychological and neuroradiological examinations, we studied a patient with svPPA who exhibited word deafness. Her auditory brainstem responses were normal, and her pure-tone audiometry threshold was almost entirely preserved for her age. However, the click counting and click fusion tests revealed a deficit in temporal auditory acuity. Auditory discrimination of verbal sounds was also disturbed. Voxel-based morphometry and region of interest (ROI)-based analyses of gray matter volume on brain magnetic resonance imaging (MRI) revealed significant atrophy in the bilateral superior temporal areas, predominantly on the left, compared to those of 10 patients with typical svPPA. These areas play an important role in verbal sound discrimination, and dysfunction in these areas might have led to word deafness in our patient. This case provides further evidence that the extent of lesions in each PPA patient affects the type of hearing impairment experienced.